Geochemical contrast between Beroga (Kuala Kelawang pluton) and Semenyih (Kuala Lumpur pluton) granites in Kuala Kelawang area, Negeri Sembilan - Ghani, Azman Abd; Sofian-Azirun, Mohd; Ramli, R.; Hashim, Rosli; Rahman, N.I.; Zainuddin, Z.A. (Geological Society of Malaysia, 2008)
Geochemical data of both Semenyih and Beroga granites, in the central part of Main Range Granite, show that they are madeup of different magma pulses. The Beroga granite is more basic, containing 67.22 - 68.02% SiO2, whereas the Semenyih granite consists of more evolved rock (SiO2 : 70.36 to 73.48%). Both are S-type granite which suggests that the source rocks were metasediments. Geochemically, they are part of the Main Range Granite. The Semenyih granite is charcterised by high Rb/Sr ratio, which suggests that the magma is highly evolved and contains less enclaves compared to the Beroga granite.